2002
DOI: 10.1074/jbc.m201914200
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Acidic Coiled-coil-containing Protein 4 Interacts with Centrosomal AKAP350 and the Mitotic Spindle Apparatus

Abstract: AKAP350 is a multiply spliced family of 350 -450-kDa protein kinase A-anchoring proteins localized to the centrosomes and the Golgi apparatus. Using AKAP350A as bait in a yeast two-hybrid screen of a rabbit parietal cell library, we have identified a novel AKAP350-interacting protein, transforming acidic coiled-coil-containing protein 4 (TACC4). Two-hybrid binary assays demonstrate interaction of both TACC3 and TACC4 with AKAP350A and AKAP350B. Antibodies raised to a TACC4-specific peptide sequence colocalize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…To date, only a few coiled-coil structures have been found to be involved in centrosome localization and, yet, these structures usually vary in length or share low homology in primary sequences. We have noted that the coiled-coil region of TACC4 is similar to that of Su48 in length and can target the protein to the centrosome by association with a related centrosome anchor protein AKAP350 (28). However, the coiled coil of Su48 shares little homology to the comparable region of TACC4 or other centrosomal proteins.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few coiled-coil structures have been found to be involved in centrosome localization and, yet, these structures usually vary in length or share low homology in primary sequences. We have noted that the coiled-coil region of TACC4 is similar to that of Su48 in length and can target the protein to the centrosome by association with a related centrosome anchor protein AKAP350 (28). However, the coiled coil of Su48 shares little homology to the comparable region of TACC4 or other centrosomal proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Positive results were recorded if ␤-galactosidase assay was positive within 3 h. All constructs were tested for auto-activation. We used an established AKAP350-interacting protein, TACC3, cloned into pAD vector as a positive control for direct interaction (31). Results are representative of three independent experiments.…”
Section: Yeast Two-hybrid Assaysmentioning
confidence: 99%
“…Mass spectrometry analysis of different AKAP350A-scaffolded protein complexes revealed that two centrosomal proteins, Cdk5RAP2 and Cep170, interact specifically with AKAP350A constructs containing the MTNC-promoting region and therefore likely play roles in regulation of microtubule nucleation. Another centrosomal protein, Cep68, associated with AKAP350A distal to the promoting region in the far C-terminal sequence of AKAP350A, which also contains the PACT domain and the binding region for TACC3 (31).…”
Section: Akap350a Promotes Microtubule Nucleationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pericentrin and another anchoring protein, AKAP350/450, both target PKA and protein kinase C (PKC) to sites within the centrosome. However, the latter can also anchor the additional binding partners PP1, PP2B, phosphodiesterase (PDE), protein kinase N (PKN), TACC3 and CLIC4 (Diviani et al, 2000;Chen et al, 2004;Steadman et al, 2002). The repertoire of AKAP targeting may also be increased through transcriptional regulation.…”
mentioning
confidence: 99%